2007
DOI: 10.1016/j.jtcvs.2006.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of giant left atrial diverticulum

Abstract: pending. On the basis of the currently available literature on the fields of vascular and general thoracic surgery, we think that thoracoscopy is safe if performed by experienced surgeons. Even when we are reporting a single case, we think that the Harmonic scalpel is a tool that can be safely used for the division of vascular rings of appropriate sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Previous reports regarding accessory LA appendages or diverticula suggested that these out-pouching structures might be associated with an increased risk of thromboembolic disease because of low flow and turbulence within the sac-like structure [5,16]. There have been a few case reports about the aggressive treatment of these out-pouching structures that were regarded as a potential cardioembolic source [10,18,19]. We hypothesized that if the LA out-pouching structures were a possible embolic source, the prevalence of these structures would be higher in patients who were classified as stroke with undetermined etiology than in others that were differently classified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports regarding accessory LA appendages or diverticula suggested that these out-pouching structures might be associated with an increased risk of thromboembolic disease because of low flow and turbulence within the sac-like structure [5,16]. There have been a few case reports about the aggressive treatment of these out-pouching structures that were regarded as a potential cardioembolic source [10,18,19]. We hypothesized that if the LA out-pouching structures were a possible embolic source, the prevalence of these structures would be higher in patients who were classified as stroke with undetermined etiology than in others that were differently classified.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of dual-source CT, small left atrial diverticula are detected as common anatomic structures with a prevalence of more than 30% [3]. There have been isolated reports of very large left atrial diverticula that extend to the apex of the heart over the ventricular surface [1,2,4,5]. To our knowledge, this is one of the largest left atrial diverticula to be reported.…”
Section: Commentmentioning
confidence: 99%
“…Giant left atrial diverticula are usually diagnosed in childhood because of the appearance of symptoms [1,2] and have even been detected using prenatal fetal echocardiography [4]. Diagnosis can be delayed until adulthood when a patient has only the nonspecific symptom of chest tightness without the other characteristic symptoms of concomitant atrial fibrillation, left atrial thrombus, mitral regurgitation, or other cardiac malformations.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…While aneurysms of the atrial septum are frequently observed, atrial diverticula especially those of the left atrium represent a rare malformation. Only a limited number of cases has been reported in the literature 2–4 . Both identities are distinguished by their wall structure and motion.…”
mentioning
confidence: 99%